Neck muscle fatigue differentially alters scapular and humeral kinematics during humeral elevation in subclinical neck pain participants versus healthy controls. (April 2017) - Zabihhosseinian, Mahboobeh; Holmes, Michael W.R.; Howarth, Samuel; Ferguson, Brad; Murphy, Bernadette
Abstract: Background: Scapular orientation is highly dependent on axioscapular muscle function. This study examined the impact of neck muscle fatigue on scapular and humeral kinematics in participants with and without subclinical neck pain (SCNP) during humeral elevation. Methods: Ten SCNP and 10 control participants performed three unconstrained trials of dominant arm humeral elevation in the scapular plane to approximately 120 degrees before and after neck extensor muscle fatigue. Three-dimensional scapular and humeral kinematics were measured during the humeral elevation trials. Results: Humeral elevation plane angle showed a significant interaction between groups (SCNP vs controls) and trial (pre- vs post-fatigue) ( p  = 0.001). Controls began the unconstrained humeral elevation task after fatigue in a more abducted position, ( p  = 0.002). Significant baseline differences in scapular rotation existed between the two groups (Posterior/Anterior tilt, p  = 0.04; Internal/External Rotation, p  = 0.001). Discussion: SCNP contributed to altered scapular kinematics. Neck muscle fatigue influenced humeral kinematics in controls but not the SCNP group; suggesting that altered scapular motor control in the SCNP group resulted in an impaired adaption further to the neck muscle fatigue.